2006
DOI: 10.1002/jrs.1509
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectra of the neutral and anionic radical semiquinones of flavin adenine dinucleotide in glucose oxidase revisited

Abstract: Flavin radical semiquinones are intermediates in important physiological processes. Resonance Raman (RR) spectroscopy is an important tool to determine the interactions between these radical intermediates and their protein environment that regulate their reactivity and role in the reaction mechanisms. RR spectra of flavin radical semiquinones have been available for several flavoproteins, and those in the glucose oxidase (GO) seem significantly different from all the other available data. Since GO is often use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…3 is not assignable to the UVRR band of Trp ÐC because no intense band was observed in this region of the reported spectra by Johnson et al 17 The most probable assignment is that the band is due to FAD Ð . Schelvis et al 18 reported visible RR spectra of FAD in GOD, which exhibited a prominent RR band at 1330 cm 1 . Figure 4 shows the picosecond time-resolved UVRR spectra of GOD measured with the 240-nm probe pulse.…”
Section: Resultsmentioning
confidence: 99%
“…3 is not assignable to the UVRR band of Trp ÐC because no intense band was observed in this region of the reported spectra by Johnson et al 17 The most probable assignment is that the band is due to FAD Ð . Schelvis et al 18 reported visible RR spectra of FAD in GOD, which exhibited a prominent RR band at 1330 cm 1 . Figure 4 shows the picosecond time-resolved UVRR spectra of GOD measured with the 240-nm probe pulse.…”
Section: Resultsmentioning
confidence: 99%
“…Asakawa et al 281 have applied a previously developed Raman linear intensity difference method to study Trp189 in bacteriorhodopsin, a transmembrane protein which acts as a light-driven proton pump. Finally, Schelvis et al 283 revisited the resonance Raman spectra of the neutral and anionic radical semiquinones of flavin adenine dinucleotide in glucose oxidase. In order to characterize the protein structure of human myeloperoxidase and its Met243Thr and Asp94Val mutants Brogioni et al 282 have undertaken a comprehensive resonance Raman study as a function of excitation wavelength and incident laser polarization.…”
Section: Biochemical Applicationsmentioning
confidence: 99%